Current Management of Renal Cell Carcinoma and Targeted Therapy - Canda, A Erdem; Kirkali, Ziya (Urology Journal, 2009)
Introduction: The aim of this review is to provide an update on the current management of renal cell carcinoma (RCC) and targeted molecular therapy for metastatic RCC. Materials and Methods: A Pubmed database search was performed using the keywords â€œrenal cell carcinoma, treatment, management, localized disease, metastatic disease and targeted therapyâ€ covering 1995 to 2006. The most recent articles published having clinical relevance were reviewed for the preparation of this paper. Results: Surgery is considered as the only curative treatment for localized RCC. Currently, open radical nephrectomy is mainly performed in patients with large tumor size, locally advanced tumors and tumor thrombus extending into the vena cava. Nephron sparing surgery (NSS) is the most commonly performed procedure with excellent local cancer control in small, resectable renal tumors. Increasingly, laparoscopy is being performed and now recommended for early-stage RCCs unsuitable for NSS. Laparoscopic radical nephrectomy seems to be providing long-term cancer control comparable to open radical nephrectomy. Laparoscopic NSS is now available particularly in patients with a relatively small and peripheral renal tumor. The current therapy for metastatic RCC is inadequate and surgery is an important component of the treatment with combined immunotherapy in which response rates remain at about 15% to 25%. In the past several years, significant advances in the underlying biological mechanisms of RCC development have permitted the design of new molecularly targeted therapeutics such as antibodies, tumor vaccines, anti-angiogenesis agents and small molecule tyrosine kinase inhibitors in order to improve treatment options. Conclusion: Surgery is the only curative treatment for localized RCC and NSS cures most of the patients with early-stage disease. Currently laparoscopy is recommended for early-stage RCCs unsuitable for NSS. Better understanding of the molecular pathways of carcinogenesis in RCC leads to the discovery of new drugs which can prolong survival in metastatic RCC.